Engaging scientists in science communication: The effect of social proof and meaning. (1st January 2018) - Hu, Saiquan; Li, Zhengfeng; Zhang, Jin; Zhu, Junming
Abstract: Science communication helps the general public understand science breakthroughs, making them support evidence-based decision making. Therefore, science communication is of paramount importance for issues that closely relate to the public, such as sustainability, climate change, and environmental behaviors. The degree of scientists' involvement in science communication, however, is often inadequate in China. This article considers scientist engagement as a two-stage process consisting of participation and effort and then explores the causal effects of social factors in this process. Based on a field experiment with Chinese scientists, we find that, as social proof, information of peers' engagement significantly increases scientists' participation, but not their real efforts made in science communication; in-group meaning, which emphasizes the benefits of scientist communication to the science community, does not induce more participation but significantly increases average efforts of participants. A combination of social proof and in-group meaning can lead to greatest efforts of scientists to communicate with the general public. Highlights: Science communication is important to sustainability and climate action. Scientist public engagement is separated into two steps: participation and effort. How social factors affect public engagement is tested in a large field experiment. Social proof significantly increases scientist participation but not their efforts. In-group meaning significantly improves scientist effort but not their participation.